Andean non‐volant small mammals: A dataset of community assemblages of non‐volant small mammals from the high Andes - Edgardo M. Rengifo; Jorge Brito; J. Pablo Jayat; Raisa Cairampoma; Agustina Novillo; Natali Hurtado; Ignacio Ferro; Cesar E. Medina; Alfonso Arguero; Sergio Solari; Jose Urquizo; Ariatna Villarreal; et al. (Ecology, 2022)
Information from diversity inventories was used to study patterns of biodiversity and species distribution, to identify potential priority areas for conservation, and to guide future sampling efforts. In this context, we compiled information on non‐volant small mammal communities from the high Andes (>2000 m). Here, we present an open source dataset containing information on diversity (species composition, number of individuals captured), inventory design (type of traps, sampling efforts), and environment (habitat) for both unpublished and published information. This study covers 630 mammalian communities, geographically distributed throughout the Andes in Venezuela, Colombia, Ecuador, Peru, Bolivia, Argentina, and Chile. We compiled a total of 26,412 individual records belonging to 240 species; the order with greatest number of records was Rodentia ( n = 25,319, 96.06%), followed by Didelphimorphia ( n = 373, 1.42%), Eulipotyphla ( n = 358, 1.36%) and Paucituberculata, ( n = 307, 1.16%). Andean non‐volant small mammal communities harbor a range from 1 to 17 species, with 93.06% of sites being composed of one to five species, 27.78% of sites with species richness varying from 6 to 10 species, and 4.17% sites composed of more than 10 species. Multiple sampling methods were used to survey non‐volant small mammals; the most representative methods were snap‐traps and Sherman traps, or a combination of both, in more than 81% of the studies. This data paper represents the first large dataset of faunal species inventories for the Andes. There are no copyright restrictions associated with the use of this dataset. Please cite this data paper when its data are used total or partially in research or teaching.